PERAN TAMAN PENDIDIKAN AL-QUR'AN DALAM MENINGKATKAN KUALITAS KEMAMPUAN BACA TULIS AL-QUR'AN - Arista Dwi Nurchasanah; S Sugiyat; S Sukari (Institut Islam Mamba'ul 'Ulum Surakarta, 2021)
The purpose of this study was to determine the application of learning and the role of the Al-Qur'an Education Park in improving the quality of reading and writing the Qur'an at TPQ Al- Furqon Dukuh Tangkil Baru, Manang, Grogol and to find out what obstacles were experienced in learning. In this research using qualitative methods through interview techniques, observation and also strengthened by documentation. The subject in the study was TPQ Al-Furqon in Dukuh Tangkil Baru, Manang, Grogol. Meanwhile, data analysis uses data reduction, data presentation, conclusion drawing/verification. The results of this study indicate that the application of learning at TPQ Al- Furqon is well-systemized according to the vision, mission and goals that have been prepared. The role of TPQ in improving the quality of reading and writing the Qur'an is very important by moving well-organized management, choosing the right method, supporting facilities and infrastructure, and the role of educators who are able to improve the quality of reading and writing skills in children. The obstacles that occur when implementing reading and writing the Qur'an are caused by several factors such as low children's learning motivation, lack of education in the family and also students who still like to play so that the focus on learning is still lacking.